New replacement name for a homonym in Lepeophtheirus (Crustacea: Copepoda: Caligidae) - Kakui, Keiichi; Uyeno, Daisuke (Zootaxa, 2020)
Markevich (1940) established Pseudolepeophtheirus Markevich, 1940 for Pseudolepeophtheirus longicauda Markevich, 1940 based on copepods collected from the pleuronectid fish Platichthys stellatus (Pallas, 1787). Dojiri & Ho (2013) synonymized the genus and the species with Lepeophtheirus Nordmann, 1832 and Lepeophtheirus parvicruris Fraser, 1920, respectively. Later, Homma et al. (2020) resurrected Markevich’s species as a member of Lepeophtheirus, i.e., as L. longicauda (Markevich, 1940). The last component of the names of both genera is ‘phtheirus’ (transliterated from the Greek φθειρ; Nordmann 1832: 30), a masculine noun, and thus under Article 30.1.2 of the International Code of Zoological Nomenclature (hereinafter, Code; International Commission on Zoological Nomenclature 1999), both generic names are also masculine. The species-group name longicauda might be regarded as either a noun in apposition or as an adjective in the feminine gender, and Markevich (1940) did not specify his intention in this regard. Bearing in mind that ‘cauda’, meaning ‘tail’, actually is a feminine Latin noun and that Markevich did not change the final ‘-a’ to ‘-us’ to match the masculine gender of the genus, we deem that longicauda Markevich, 1940 is a noun in apposition, a position supported by Article 31.2.2 of the Code.